Cellular and physiological responses to drought stress in Aegilops tauschii genotypes - Falaknaz, Mehran; Alaami, Ali; Mehrabi, Aliashraf; Sabouri, Atefeh; Kahrizi, Danial; Karimi, Naser (Cellular and Molecular Biology, 2019)
Drought stress is one of the most important limiting factors in crop yield through impact on the cellular and physiological functions of the plant. Therefore, the study of physiological responses of plants can help to better understanding the drought tolerance mechanisms. In this experiment, 125 wild diploid wheat genotypes of Aegilops tauschii were evaluated for the physiological responses under rainfed and supplemental irrigation conditions. The physiological characteristics such as leaf relative water content (RWC), excised leaf water retention (ELWR), relative water loss (RWL), chlorophyll a, chlorophyll b, total chlorophyll, carotenoids, ion leakage, membrane stability index (MSI) and proline content were measured. The results showed that the higher proline content, lower chlorophyll degradation rate and low amount of the membrane stability index (MSI) may inhibit the grain yield reduction under rainfed conditions. It was also found that the lower ion leakage due to the low cell membrane damage may led to the higher yield under rain-fed conditions. The results of regression analysis in both rainfed and supplemental irrigation conditions showed that proline content and total chlorophyll were introduced into the model, and explained the most variation in the grain yield. So, considering the above traits, the genotypes 16, 22, 43, 66 and 106 seems to be more drought tolerant and could be exploited in wheat breeding programs after further assessments.